European spaces and the Roma: Denaturalizing the naturalized in online reader comments. Issue 3 (June 2018) - Catalano, Theresa; Fielder, Grace E
With the entry of several Eastern European nations into the European Union (EU), a 'third' space has developed in the discourse for nations perceived as not fully integrated 'inside' the EU system. This article investigates the construction of this 'third space' in the resultant 'moral panic' about undesired immigration from other EU countries and its potential drain on the social services of the United Kingdom and links it to Euroskeptic discourse in British media. The article uses construal operations from cognitive linguistics combined with critical discourse studies as a way of denaturalizing the discourse in online comments that focus on the Bulgarian/Romanian immigration issue which we then connect to anti-Roma discourse. Results reveal a view of the United Kingdom as contaminated by Roma and underscore the need for novel metaphors to be countered before they become entrenched and used as tools for political propaganda.